2018
DOI: 10.1177/0731684418819822
|View full text |Cite
|
Sign up to set email alerts
|

Review on the methodologies adopted to minimize the material damages in drilling of carbon fiber reinforced plastic composites

Abstract: The applications of carbon fiber reinforced plastic materials have increased widely in the fields of aerospace, automotive, maritime, and sports equipment because of their excellent mechanical properties. Machining of carbon fiber reinforced plastics has a considerably more complex effect on drilling qualities than machining of conventional metals and their alloys due to the nonlinear, inhomogeneous, and abrasive nature of CFRPs. This article addresses the methodologies that have been adopted to minimize the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 97 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Then, the surface quality of holes is influenced by cutting conditions and tool geometries. 25,26 Several experimental studies confirmed that including the most critical factors in determining the surface roughness is the feed speed. [27][28][29] Besides that, many authors confirmed that there is an increase in the surface roughness by the increase of the number of cutting edges and the helix angle.…”
Section: Introductionmentioning
confidence: 93%
“…Then, the surface quality of holes is influenced by cutting conditions and tool geometries. 25,26 Several experimental studies confirmed that including the most critical factors in determining the surface roughness is the feed speed. [27][28][29] Besides that, many authors confirmed that there is an increase in the surface roughness by the increase of the number of cutting edges and the helix angle.…”
Section: Introductionmentioning
confidence: 93%
“…A software model developed in-house considering moisture absorption parameters like moisture content at a given time within the initial absorption curve, that is, linear portion, slope of linear portion, diffusion coefficient, and so on, to predict the maximum or saturation moisture content and also the time of saturation mainly using equations (1) and (2). It was observed that the predicted results and the experimental results were in close correlation for conditions 70 C/85% RH and 55 C/100% RH.…”
Section: Moisture Absorption Behaviormentioning
confidence: 99%
“…Use of carbon fiber-reinforced plastic (CFRP) composites is increasing nowadays due to reduced weight along with the increase in strength and stiffness. 1,2 These widespread applications are mainly in aerospace and automotive industries. In their service life, composite structures are usually subjected to a variety of environmental situations, such as hygrothermal, chemical environments, UV radiation, biological conditions, and so on, which produces degradation in material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, several difficulties are encountered during these machining processes; which include high tool wear, fraying of composites, formation of burs and fibre-matrix interface damages. 10,11 Due to the existence of such difficulties, there arises a demand for a cost-effective and minimum damage material removal solution for FRP composites. 12 Machining using abrasives, typically grinding operations, have shown the ability to meet precision requirements.…”
Section: Introductionmentioning
confidence: 99%